2014
DOI: 10.1021/jp412793w
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Supramolecular Self-Assembly of Stilbene Derivatives with Ester Groups: Molecular Symmetry and Alkoxy Substitution Effect

Abstract: In this paper, four stilbene derivatives substituted with ester groups were synthesized and their two-dimensional (2D) self-assembled behaviors were investigated by scanning tunneling microscopy (STM) on the highly oriented pyrolytic graphite (HOPG) surface. The four target molecules are different in the symmetrical properties and the length of substituted alkoxy chains which extremely influence the self-assembly of these molecules on graphite surface. As a result, we obtained four kinds of nanostructures incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…It is therefore a question of fundamental importance to determine the influence of the number, length and position of these substituents on the spontaneous organization of molecules. STM techniques have been frequently used for such investigations in monolayers of organic molecules of very different chemical natures, for example alkyl (alkoxy) derivatives of: benzoic acids [18], thiophene [15,16,[19][20][21][22], annulene [23,24], fluorenone [25,26], stilbene [27], and others [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore a question of fundamental importance to determine the influence of the number, length and position of these substituents on the spontaneous organization of molecules. STM techniques have been frequently used for such investigations in monolayers of organic molecules of very different chemical natures, for example alkyl (alkoxy) derivatives of: benzoic acids [18], thiophene [15,16,[19][20][21][22], annulene [23,24], fluorenone [25,26], stilbene [27], and others [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly of solution processable semiconducting molecules is usually governed by interactions between their conjugated cores and interdigitation of the solubilizing alkyl (or alkoxy) substituents [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. From this point of view, the compounds described here constitute an interesting, albeit complex case in which the formation of the 2D supramolecular organization is governed by several factors associated with the molecule topology.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that long alkyl chains can more easily adsorb to the surface via van der Waals interactions. 31 Other than the alkane−substrate interaction, the long alkyl chain also can form interdigitated alignment to modify the distance between molecules. It is important to investigate the influence of length and number of substituted alkyl chain on the strength of van der Waals interactions for well-defined 2D self-assembly structures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Precursor compounds H1−H4 were synthesized according to our previous work. 31 Self-Assembly at the Interface. As shown in Scheme 1, compounds 1 and 2 have four substituted alkoxyl chains with different length, terminated with carboxylic acid groups, while compounds 3 and 4 have only three alkoxyl chains with different length, also terminated with carboxylic acid groups.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation